Analysis Business Process of Package Delivery Services Using a Business Process Reengineering Approach at ABC Company - Yekti Condro Winursito; Isna Nugraha; Lanang Adnanta Irasyddin; Bryan Reinaldo (Jurnal Serambi Engineering, 2026)
Due to this fast growth in the logistics industry, the demand for high-speed and reliable delivery services is increasing. This paper is based on a qualitative case study in which the current delivery process at ABC Company is studied, and recommendations are provided for process improvement. Data were collected through observations, interviews, Value Stream Mapping (VSM), VOC, Voice of Business (VOB), and PICK Chart analysis. Based on the analysis, the eight types of waste and the Process Cycle Efficiency (PCE) of 25% were found, which refers to many non-value-adding activities. The most prominent problems were delay in delivery, damaged packages, wrong destination, incomplete address, and poor shipment verification. After improvement, the process was reduced from eight stages to four, and the lead time was decreased from 64 hours to 37 hours. Thus, it increased logistics process efficiency by approximately 42%. Value Stream Mapping has been instrumental in supporting process improvement, courier performance enhancement, and customer satisfaction.